Vaccination coverage of general practitioners: a cross-sectional study from Greece. (April 2020) - Kalemaki, D.; Karakonstantis, S.; Galanakis, E.; Lionis, C.
Abstract: Objectives: Vaccination coverage of general practitioners (GPs) is important for their own and for their colleagues' and patients' protection and has been associated with the coverage of the general population. Our study aims to evaluate the vaccination practices of GPs in Crete, Greece. Study design: Cross-sectional, questionnaire-based survey. Methods: All practicing GPs in Crete (n = 294) were surveyed either by questionnaires or by phone call. We assessed the vaccination coverage and practices for influenza, measles, hepatitis B, and pertussis (booster Tdap dose) and the reasons for nonvaccination for influenza. Results: A total of 260 (88% response rate) GPs participated. Vaccination rates were 56% for influenza (current season), 26% for measles (two doses), 68% for hepatitis B (three doses), and 18% for the booster dose with Tdap. Negligence (47%) and perceived low risk (29.6%) were the most common reasons for nonvaccination for influenza. History of natural measles infection was reported by 169 (65%) GPs, but none of the interviewed 31 provided laboratory confirmation. GPs with self-reported natural measles infection were less vaccinated than their peers (10% vs 55%, P  < 0.001). Finally, 23 of 130 (18%) GPs contacted by phone falsely reported vaccination with Tdap in their childhood, when Tdap was not yet available. Conclusion: This study revealed insufficient vaccination rates and misconceptions among GPs that should be the focus of future evidence-based interventions with potential to significantly improve vaccination coverage of GPs and indirectly of their patients. Highlights: Vaccination coverage of general practitioners (GPs) in Crete is low. Many GPs falsely reported Tdap vaccination in their childhood. Nonvaccination for measles was driven by unconfirmed immunity by past infection. Negligence was a major reported reason for nonvaccination for influenza. Informative interventions and on-site vaccination may improve vaccination coverage.